2016
DOI: 10.1002/biof.1345
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 targeting by polyphenols: Novel therapeutic strategy for melanoma

Abstract: Melanoma or malignant melanocytes appear with the low incidence rate, but very high mortality rate worldwide. Epidemiological studies suggest that polyphenolic compounds contribute for prevention or treatment of several cancers particularly melanoma. Such findings motivate to dig out novel therapeutic strategies against melanoma, including research toward the development of new chemotherapeutic and biologic agents that can target the tumor cells by different mechanisms. Recently, it has been found that signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 275 publications
(342 reference statements)
2
25
0
Order By: Relevance
“…STAT3 is a member of STAT family of transcription factors, which plays a key role in cell apoptosis, proliferation, metastasis, angiogenesis, and immune escape. 18-20 Downregulation of the protein is consistent with the observation of cell apoptosis and proliferation inhibition. Because apoptosis was observed in the absence of caspase 3, it remains to be explored whether GSSG liposomes caused a caspase 3–independent apoptosis.…”
Section: Resultssupporting
confidence: 83%
“…STAT3 is a member of STAT family of transcription factors, which plays a key role in cell apoptosis, proliferation, metastasis, angiogenesis, and immune escape. 18-20 Downregulation of the protein is consistent with the observation of cell apoptosis and proliferation inhibition. Because apoptosis was observed in the absence of caspase 3, it remains to be explored whether GSSG liposomes caused a caspase 3–independent apoptosis.…”
Section: Resultssupporting
confidence: 83%
“…More-recently, Momtaz et al [149] has shown the influence of Ole on melanoma. Melanoma is certainly one of the most aggressive skin cancers, due to its progression to drug resistance and its organ dissemination.…”
Section: Multiple Checkprotein Of Transcription Of Oleuropeinmentioning
confidence: 97%
“…STAT3 can affect the metastasis of cells in many ways. 20,21 Among them STAT3/mmp2 pathway is a common pathway. We wondered if miR-337 could regulate the metastasis of melanoma cells by suppressing STAT3/mmp2 pathway.…”
Section: Mir-337 Inhibits the Metastasis Of Melanoma Cellsmentioning
confidence: 99%